Karakteristik Budidaya Kakao (Theobroma Cacao L.) Pada Perkebunan Rakyat Di Kecamatan Panti Kabupaten Pasaman - Riska Agian Putri; Wulan Kumala Sari; Dede Suhendra (Jurnal Riset Perkebunan, 2021)
Cacao (Theobroma cacao L.) is one of the plantation crop that has high economic value. Therefore it is important to carry out cacao cultivation as recommended. The objective of this study was to collect data on the cultivation characteristics on smallholder cacao plantations where located in Panti Sub-district, Pasaman District. This research was conducted from August until November 2021 in Panti Sub district, Pasaman District the present research was carried out using a survey method by purposive sampling, with the criteria that cacao crops have produced and the sample includes 10% of the smallholder cacao crops area in Panti Sub-district, pasaman District. The aspects that are included in the characteristics of cacao cultivation are in terms of land preparation, crop maintenance, the techniques for pest and disease control, as well as aspects of harvest and yield. The results showed that 80% of cacao farmers in Panti Sub-district had carried out cacao cultivation according to Puslitkoka standards, but its 20% have not carried out cacao cultivation according to the recommendations, including the aspects of land preparation, crops maintenance, and harvestthat were not appropriate the origin of planting material was unclear, unknown of the clone types, pest and disease attacks are still high and sanitation activitie. Are irregular.